Современные подходы к терапии гиперплазии эндометрия у женщин в перименопаузальном периоде - Кузьмина, И.Ю. (Таврический медико-биологический вестник, 2012)
Проведено дослідження метаболітів эстрону (2-гідроксиестрону – 2-OHEi і 16α-OHEi) у сечі жінок
у перименопаузі. Застосування препарату індол-ф® протягом 4 місяців по 2 капсули 2 рази на день у жінок
в перименопаузальному періоді призводить до зниження рівня загальних естрогенів в 1,3 рази, а також
до статистично значимого зниження рівня 16α-OHEi, підвищення співвідношення 2-OHEi/16 α-OHEi, що
може бути патогенетичним обґрунтуванням його лікувального впливу при гіперпластичних процесах
эндометрію. The conducted research of the metabolites by estronum (2-gidroksiestron – 2-OHEi and 16 α-OHEi)
is carried out in urine at women in perimenopausal period. Preparation application of indol-F® during 4 month
on 2 capsules 2 times a day at women in perimenopausal period leads to depression of level of the general
estrogens in 1,3 times, and also to statistically significant depression of level 16 α-OHEi, to interrelation rising
2-OHEi/16 α-OHEi, that can be a pathogenetic substantiation of its medical influence at hyperplastic
processes of endometrium.